A Short Note about some Useful Documents for Diachronical Studies of Non-Semitic Ethiopian Languages - Rouaud, Alain (Aethiopica, 2009)
The collection of manuscripts preserved in the Oriental Manuscripts Department of the French Bibliothèque nationale contains documents about some thirty non-semitic languages spoken in Ethiopia which belong mainly to the d’Abbadie collection. Their exceptional age (they date back to the mid-19th century) gives them an incomparable historical value. I try in this short note to assess the use which has already been made of these documents by éthiopisants and to draw up the list of those which have not yet been used.